Moral Judgment and its Impact on Business-to-Business Sales Performance and Customer Relationships - Schwepker, Charles H., Jr. (Journal of business ethics, 2011)
For many years, researchers and practitioners have sought out meaningful indicators of sales performance. Yet, as the concept of performance has broadened, the understanding of what makes up a successful seller, has become far more complicated. The complexity of buyer–seller relationships has changed therefore as the definition of sales performance has expanded, cultivating a growing interest in ethical/unethical actions since they could potentially have impacts on sales performance. Given this environment, the purpose of this study is to explore the impact of moral judgment on sales performance and sellers engaging in a customer-oriented selling approach. Specifically, by utilizing a sample of 345 business-to-business salespeople, this study examines the relationships between moral judgment, customer-oriented selling, and outcome and behavior based performance. Results, managerial implications, and opportunities for future research are provided.